INTEGRATION OF ACEH'S LOCAL WISDOM VALUES AND ISLAMIC RELIGIOUS COMMUNICATION - Bahriar Syah (Prodi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Dharmawangsa, 2026)
The high divorce rate in Bireuen Regency demands serious attention from Islamic religious counselors, particularly in premarital guidance activities. This study analyzes the integration model of Acehnese local wisdom values in Islamic religious counselor communication, measures its effectiveness, and identifies challenges and optimization strategies. The research method uses a qualitative-descriptive approach with case studies. Data collection techniques include observation, interviews, documentation, and focused group discussions to obtain comprehensive data on premarital guidance practices. The research results show that local wisdom values such as peusijuek (blessing ritual), hadih maja (traditional proverbs), and the tuha peut system (traditional leadership) are able to strengthen religious messages when contextually integrated in premarital counseling. The integration of these values has proven to increase participants' understanding and acceptance of guidance materials. However, the study identifies several significant obstacles, namely conventional counseling methods, limited implementation time, and minimal contextual training for counselors in integrating local values with Islamic teachings. The research recommends developing a da'wah communication model oriented toward local culture as a strategy to improve the effectiveness of premarital guidance. This model is expected to contribute to building sakinah families and reducing divorce rates in Bireuen Regency.